Racikan Strategi Pemberian Kredit di Bank Perkreditan Rakyat - Anak Agung Gede Agung Adnya Prasta; Luh Putu Mahyuni (Universitas Pendidikan Nasional, 2019)
ABSTRACTAlong with the decline in interest rates given while the interest rates of third party funds did not experience a decline from the previous year. This indicates that there is an inverse comparison between the savings interest rate and the loan interest rate, where the comparison should be directly proportional to the interest rate of the savings and the interest rate on the loan. This research was conducted at PT. BPR. Balaguna Perasta, whose address is batutabih no. 99x Klungkung District, Klungkung Regency, Bali Province. The reason for conducting research is because of the level of competition in tight lending rates in line with the reduction in LPS (Deposit Insurance Corporation) interest rates, besides that this research was conducted because of the loan interest rates given by PT. BPR Balaguna Perasta is smaller than the average market interest rate. Data type consists of quantitative data and qualitative data collected from primary and secondary data, through data collection techniques, documentation and interview studies to 3 informants, and data validity testing techniques using triangulation with sources and using quantitative and qualitative analysis techniques. With the calculation of the average interest rate on BPR loans in Klungkung Regency at 21.6% pa, the channeling of loans provides an average loan interest rate of 19.1% pa (according to the 2018 financial report), and based on the calculation of the base landing rate above is obtained at 20.77%, so the interest rate determination made by the Rural Credit Bank (BPR) Balaguna Perasta in Klungkung Regency is not yet ideal. In giving and lending to banks, it is always based on the rules / procedures for granting credit by applying the precautionary principle. Especially, it has applied the 5'C principle which includes analysis of character, capacity, capital, collateral, condition of economic in addition to the procedure of lending in accordance with Bank Indonesia regulations, namely credit application requirements, credit granting limits, loan interest rates, and all sanctions in accordance with regulations specified. So that the Interest Rate Determination Strategy for increasing credit sales in the Balaguna Perasta Rural Credit Bank (BPR) in Klungkung Regency does not affect much in the provision of security/ineffectiveness.